Peculiarities of the distribution of rare-earth elements in the ores of some gold deposits of Eastern Transbaikalia - B. N. Abramov (Известия высших учебных заведений: Геология и разведка)
The distribution of rare-earth elements (REE) in ores of gold deposits of East Transbaikalia has shown that the ore-bearing magma chambers have different depths and degrees of differentiation. The greatest degree of differentiation was within the magmatic foci (Eu/Eu* — 0,29—0,32; Rb/Sr — 0,98—1,40), which are the sources of gold-quartz-arsenopyrite ores, the magmatic sources of the gold-quartz and gold-sulfide-quartz ores (Eu/Eu* — 0,53—0,72; Rb/Sr of 0,10 to 0,54) had lesser degree of differentiation. Magma chambers that are sources for the gold-quartz-arsenopyrite ores (Eu/Sm — 0,08—0,14), were at shallower depths than those for gold-quartz and gold-sulfide-quartz ores (Eu/Sm — 0,11—0,19). The formation of gold-quartz-arsenopyrite ores took place at the magma chambers, largely enriched in volatile components, it is indicated by the existence of a significant tetrad effects in REE patterns of (T1-4 - 0,80; 1,15; 1,16).